1975
DOI: 10.1111/j.1469-8986.1975.tb00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Habituation During Sleeping and Waking

Abstract: EEG and autonomic habituation were studied during sleep stages 2 and REM. and during awake. Repeated presentations of the same stimulus to the same subjects within sleep stages and when awake permitted evaluation of habituation between tone sets within stag 2, REM, and awake, and from sleep to awake. Forty‐six subjects were exposed to 800 Hz. 75 dB, 1‐ or 2‐sec tones, presented in sets of 20 tones. During steep, there was no habituation of the EEC response. Habituation occurred for both FPR and HRR during stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…However, our SC data show a difference between pure REM-sleep and EMDR as ORs were present and tended to show a pattern of habituation. A consistent finding has been that ORs in electrodermal measures are rare during REM-sleep (Johnson & Lubin, 1967;McDonald & Carpenter, 1975), and when they occur they do not tend to habituate (Johnson & Lubin, 1967;Johnson, Townsend, & Wilson, 1975 …”
Section: The Physiological Effects Of Emdr and Correlates Of The Em Cmentioning
confidence: 63%
“…However, our SC data show a difference between pure REM-sleep and EMDR as ORs were present and tended to show a pattern of habituation. A consistent finding has been that ORs in electrodermal measures are rare during REM-sleep (Johnson & Lubin, 1967;McDonald & Carpenter, 1975), and when they occur they do not tend to habituate (Johnson & Lubin, 1967;Johnson, Townsend, & Wilson, 1975 …”
Section: The Physiological Effects Of Emdr and Correlates Of The Em Cmentioning
confidence: 63%
“…In an attempt to confirm the lack of habituation during sleep as revealed by their earlier research, Johnson, Townsend, and Wilson (1975) recorded SRRs to a series of 20 stimuli 142 presented during stage II and REM sleep. Data from 9 participants with complete recordings did not yield unambiguous stimulus-dependent SRRs in either sleep stage, due to the infrequency of responses during REM, and either no SRRs or too much spontaneous EDA during stage II.…”
Section: Diurnal Variation and Eda In Different Sleep Stagesmentioning
confidence: 88%
“…The overall AEP, thus, is similar to the evoked K-complex in its resistance to habituation (Johnson & Lubin, 1967;Johnson et al, 1975). While habituation is generally accepted as an index of learning, there are varying theories as to how this learning occurs (Sokolov, 1960;Thompson & Spencer, 1966).…”
Section: Discussionmentioning
confidence: 87%
“…(Johnson & Lubin, 1967). In a subsequent study (Johnson et al, 1975), while habituation was found for heart rate and finger pulse response, there was again no evidence of a decreased K-complex response.…”
mentioning
confidence: 83%
See 1 more Smart Citation